Bounded rationality and voting decisions exploring a 160-year period - David Stadelmann; Benno Torgler (Fondazione Eni Enrico Mattei (FEEM), 2012)
Using a natural voting experiment in Switzerland that encompasses a 160-year period (1848-2009), we investigate whether a higher level of complexity leads to increased reliance on expert knowledge. We find that when more referenda are held on the same day, constituents are more likely to refer to parliamentary recommendations in making their decisions. This finding holds true even when we narrow our focus to referenda with a relatively lower voter turnout on days on which more than one referendum was held. We also show that when constituents face a higher level of complexity, they listen to parliament rather than interest groups.
Keywords: D03; D72; D83; H70; 330; Bounded Rationality; Voting; Referenda Attention; Rules of Thumb